Pengaruh Fasilitas Kesehatan Dan Motivasi Kerja Terhadap Kepuasan Pasien Melalui Kualitas Pelayanan Pada Unit Rawat Inap Di RSUD Haji Makassar Provinsi Sulawesi Selatan - Aznira Nurul Hidayah; Nurmiati Muchlis; Rasyidin Abdullah (Program Pascasarjana Universitas Muslim Indonesia, 2021)
Background: Measurement of customer satisfaction is an important element in providing better, efficient and more effective service. This study aims to determine the effect of health facilities and work motivation on patient satisfaction through service quality in inpatient units at Haji Makassar Hospital, South Sulawesi Province. Method: The research design used in this study was an analytic survey with a Cross Sectional Study approach. Sampling was done by total sampling method with a total sample of 68 people. Methods of data analysis using statistical analysis calculations using the SPSS program using path analysis. Results: The results showed that from the Sobel test there was a significant and positive effect of the health facility variable at t count 3.984> 1.987 and work motivation t count of 3.011> 1.987 on patient satisfaction through service quality, there was a significant effect of the health facility variable 0.000 <0.005 on satisfaction, no there is a significant effect of work motivation variable 0.155> 0.000 on patient satisfaction, there is a significant influence of the health facility variable 0.000 <0.005 and the work motivation variable 0.001 <0.005 on service quality, and there is a significant effect of the service quality variable 0.000 <0.005 on patient satisfaction. Conclusion: The conclusion of the study shows that there is an effect of health facilities and work motivation on patient satisfaction through the quality of service at Haji Makassar Hospital, South Sulawesi Province. So it is suggested to the hospital to maintain the quality of its service.